Acid-fast smear and culture of respiratory secretions, bone marrow, and stools as predictors of disseminated Mycobacterium avium complex infection. - Poropatich, C O (1987)
Disseminated infection caused by Mycobacterium avium complex (MAC) is common in patients with acquired immune deficiency syndrome and is difficult to treat because of the high degree of resistance to antimycobacterial agents. Early diagnosis and treatment may prolong survival of patients with acquired immune deficiency syndrome and MAC infection. Twenty patients with disseminated MAC infection were evaluated for recovery of the organism from bone marrow, bronchial washings or sputum, and stools before the organism was isolated in blood culture. For 40 to 67% of patients, MAC was recovered from these specimens before it was isolated in blood culture.